2020
DOI: 10.18844/cjes.v15i5.5177
|View full text |Cite
|
Sign up to set email alerts
|

Using the interactive whiteboard for teaching from the viewpoint of physics teachers in the Sultanate of Oman

Abstract: Interactive whiteboards are provided in most schools in Oman, including those in the Al-Batinah North Governorate of the Sultanate, but many are not activated. Some teachers abandon them despite their presence and prefer to use the traditional blackboard or whiteboard for teaching. This study reveals the views of physics teachers in the Al Batinah North Governorate about the use of the interactive whiteboard for teaching physics. This study adopts a descriptive approach to collecting data from 377 male and fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…Interestingly, the findings revealed that significant differences were not found in the EFL teachers' perspectives of word identification enhancement through using IWB technology to an academic degree. This finding is in harmony with several studies conducted by Taiwo and Adeniyi (2019), Alhumsi (2017), andMalkaw et al (2020). In the category of years of experience, since there have been approximately close periods in terms of this category, the findings are affected by most EFL teachers' perspectives.…”
supporting
confidence: 89%
“…Interestingly, the findings revealed that significant differences were not found in the EFL teachers' perspectives of word identification enhancement through using IWB technology to an academic degree. This finding is in harmony with several studies conducted by Taiwo and Adeniyi (2019), Alhumsi (2017), andMalkaw et al (2020). In the category of years of experience, since there have been approximately close periods in terms of this category, the findings are affected by most EFL teachers' perspectives.…”
supporting
confidence: 89%